Characterizing the limit set of perfect and public equilibrium payoffs with unequal discounting - Takuo Sugaya (Theoretical Economics, 2015)
We study repeated games with imperfect public monitoring and unequal discounting. We characterize the limit set of perfect and public equilibrium payoffs as discount factors converge to 1 with the relative patience between players fixed. We show that the pairwise and individual full rank conditions are sufficient for the folk theorem.
Keywords: C72; C73; 330; Repeated games; unequal discounting; imperfect monitoring; folk theorem